Odpowiedzi

2010-04-14T21:48:11+02:00
ZAD. 1
a) 3x+7=-5
3x=-5-7
3x= -12 / :3
x=-4
TAK
b) 2(x+6)=4
2x+12=4
2x=4-12
2x=-8/:2
x=-4
TAK
2010-04-14T21:52:26+02:00
3 * (-4) + 7 = -7 + 7 = 0
L nie jest równa P

2(-4 +6 ) = -8+6 = 2
L nie jest równa P


2a - 3= a + 1
2a + a = 3-1
3a= 2 | ; 3
a 2/3

4b+3=3b - 4
4b-3b = 4 -3
b= 1


7+3c=-5+2c
3c-2c=7-5
c=2

5d+2=3d
8d=2 | : 8
d=4


6f - 1 = f+ 2
6f-f=-1+2
5f=1 | :5
f=5
2010-04-14T21:53:46+02:00
1 A
3* (-4)+ 7=-5
-12+7= -5
-5 = -5

1 B
2((-4)+6)= -4
2* 2 = -4
4 =/ -4

2
2a - 3=a+1
2a-a=1+3
a=4

4b+3=3b-4
4b-3b=-4-3
b=-7

7+3c= -5+2c
3c-2c=-5-7
c=-12

5d+2=3d
5d-3d=-2
2d=-2/2
d= -1

6e-2=7e+5
6e-7e=5+2
-e=7/(-1)
e=-7

6f-1=f+2
6f-f=2-1
5f=1/5
f= jedna piąta